2011
DOI: 10.1167/iovs.11-7578
|View full text |Cite
|
Sign up to set email alerts
|

Deformation of the Rodent Optic Nerve Head and Peripapillary Structures during Acute Intraocular Pressure Elevation

Abstract: PURPOSE. To evaluate the effect of acutely elevated intraocular pressure (IOP) on retinal thickness and optic nerve head (ONH) structure in the rat eye by spectral domain-optical coherence tomography (SD-OCT). METHODS. Fourteen adult male Brown-Norway rats were studied under anesthesia (ketamine/xylazine/acepromazine, 55:5:1 mg/kg intramuscularly). Both eyes were imaged by SD-OCT on two baseline occasions several weeks before and again 2 and 4 weeks after the acute IOP imaging session. During the acute IOP ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 32 publications
(44 reference statements)
7
46
0
1
Order By: Relevance
“…Thickness measurements from the manual realignment procedure were not significantly different from the combined manual þ automated realignment procedure. Similar results were published by Fortune and colleagues, 25 where they reported that manual and the Spectralis built-in automated realignment procedures yield similar thickness results. However, they did not provide details about the realignment procedures used to quantify the similarity in thickness measurements that they reported.…”
Section: Discussionsupporting
confidence: 86%
“…Thickness measurements from the manual realignment procedure were not significantly different from the combined manual þ automated realignment procedure. Similar results were published by Fortune and colleagues, 25 where they reported that manual and the Spectralis built-in automated realignment procedures yield similar thickness results. However, they did not provide details about the realignment procedures used to quantify the similarity in thickness measurements that they reported.…”
Section: Discussionsupporting
confidence: 86%
“…Longitudinal measurements of peripapillary RNFLT were acquired in vivo by SD-OCT (Spectralis OCT+HRA, Heidelberg Engineering GmbH, Heidelberg, Germany) as previously described [39], [40]. After induction of general anesthesia, rats were placed on a custom-built imaging stage and kept warm with a thermostatically-controlled system (TP650, Gaymar Industries, Inc., Orchard Park, NY).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanical theory would explain the typical pie-shaped loss of RGCs and their axons that is observed in OHT models in rats and mice. Elevated IOP has been shown to cause posterior deformation of the ON head, which is more pronounced on the dorsal than in the ventral aspect, thus providing a plausible explanation for the greater susceptibility to damage in the dorsal retina (Fortune et al, 2011). In addition to this typical sectorial loss, the observation of diffuse loss could well be explained because such a constriction of axons could also affect ON fibers within the main ON head that are somehow more susceptible to pressure-induced injury.…”
Section: Oht Affects Selectively the Rgc Population In The Gclmentioning
confidence: 99%